Carbon/Alginate/Chitosan Composite as a Sorbent for Solid-Phase Extraction and Preconcentration of Cu(II) - Ahmad Akhib Ainul Yaqin; Suherman Suherman; Mudasir Mudasir; Dwi Siswanta (Universitas Gadjah Mada, 2022)
Carbon/Alginate/Chitosan Composite (CAC) as a sorbent for solid-phase extraction of Cu(II) (pre-concentration) with atomic absorption spectrometry for analysis was successfully prepared. The sorbent was made with a mass ratio of chitosan:alginate:carbon = 1:1:1. CAC sorbents were characterized using FTIR for functional group analysis while SEM-EDX characterization was performed to determine surface morphology and percentage of elements. SPE parameters were optimized for adsorption-desorption efficiency under various conditions, i.e. of pH 5, Cu(II) concentration of 4 mg/L, the flow rate of Cu(II), and Na2EDTA eluent at 5 mL/min, the volume of Cu(II) sample and Na2EDTA eluent 25 mL and 1.0 M of Na2EDTA eluent concentration. Applying CAC-based SPE for Cu(II) analysis in water samples at optimum conditions gave 80.9–83.6% recovery. In bottled drinking water samples, a pre-concentration factor of 2.5–5 times was obtained, and the Cu(II) concentration of 0.017–0.020 mg/L was detected.